An introduction to cut-off grade estimation - Rendu, Jean-Michel, 1944- (Published by Society for Mining, Metallurgy, and Exploration, Inc., 2014)
An Introduction to Cut-off Grade Estimation examines one of the most important calculations in the mining industry. Cut-off grades are essential to determining the economic feasibility and mine life of a project. Profitability and socioeconomic impact of mining operations are influenced by the choice of cut-off grades. Cut-off grades play a key role in estimating mineral reserves that can be publicly reported.